Invisible Johannesburg seen and unseen: an exploration of the imaged/imagined city - Wafer, Mary (My University, 2010)
ABSTRACT: This project has two main aims. The first and primary aim is to produce a body of paintings, which take the urban landscape of Johannesburg as subject matter. These works aim to articulate through the processes of painting the visible and invisible city, aspects of the social/urban environment that can be seen or recognised, and those that are obscured or hidden. Through an examination of african urban theory and various tropes of understanding the city, the notiot of the invisible city is revealed. The research then progresses on to an exploration of way the city has been pictured by various painters and photographers